Review on Gallium Nitride HEMT Device Technology for High Frequency Converter Applications - Nor Zaihar, Yahaya; Mumtaj Begam Kassim, Raethar; Mohammad, Awan (KOREAN INST POWER ELECTRONICS, RM 408, KOREA SCIENCE & TECHNOLOGY BLDG, 635-4, YEOKSAM-DONG, KANGNAM-GU, SEOUL, 135-703, SOUTH KOREA, 2009)
This paper presents a review of an improved high power-high frequency III-V wide bandgap (WBG) semiconductor device, Gallium Nitride (GaN). The device offers better efficiency and thermal management with higher switching frequency. By having higher blocking voltage, GaN can be used for high voltage applications. In addition, the weight and size of passive components on the printed circuit board can be reduced substantially when operating at high frequency. With proper management of thermal and gate drive design, the GaN power converter is expected to generate higher power density with lower stress compared to its counterparts, Silicon (Si) devices. The main contribution of this work is to provide additional information to young researchers in exploring new approaches based on the device's capability and characteristics in applications using the GaN power converter design.